Adolescent antecedents of maternal and paternal perinatal depression: a 36-year prospective cohort. Issue 12 (28th September 2021) - Thomson, Kimberly C; Romaniuk, Helena; Greenwood, Christopher J; Letcher, Primrose; Spry, Elizabeth; Macdonald, Jacqui A; McAnally, Helena M; Youssef, George J; McIntosh, Jennifer; Hutchinson, Delyse; Hancox, Robert J; Patton, George C; et al.
Abstract: Background: Rates of common mental health problems (depression/anxiety) rise sharply in adolescence and peak in young adulthood, often coinciding with the transition to parenthood. Little is known regarding the persistence of common mental health problems from adolescence to the perinatal period in both mothers and fathers. Methods: A total of 393 mothers (686 pregnancies) and 257 fathers (357 pregnancies) from the intergenerational Australian Temperament Project Generation 3 Study completed self-report assessments of depression and anxiety in adolescence (ages 13–14, 15–16, 17–18 years) and young adulthood (ages 19–20, 23–24, 27–28 years). The Edinburgh Postnatal Depression Scale was used to assess depressive symptoms at 32 weeks pregnancy and 12 months postpartum in mothers, and at 12 months postpartum in fathers. Results: Most pregnancies (81%) in which mothers reported perinatal depression were preceded by a history of mental health problems in adolescence or young adulthood. Similarly, most pregnancies (83%) in which fathers reported postnatal depression were preceded by a preconception history of mental health problems. After adjustment for potential confounders, the odds of self-reporting perinatal depression in both women and men were consistently higher in those with a history of persistent mental health problems across adolescence and young adulthood than those without (ORwomen 5.7, 95% CI 2.9–10.9; ORmen 5.5, 95% CI 1.03–29.70). Conclusions: Perinatal depression, for the majority of parents, is a continuation of mental health problems with onsets well before pregnancy. Strategies to promote good perinatal mental health should start before parenthood and include both men and women.